PENGEMBANGAN PENUNTUN PRAKTIKUM BERDASARKAN UJI ORGANOLEPTIK TAPAI BIJI CEMPEDAK SUBMATERI PRODUK BIOTEKNOLOGI KONVENSIONAL KELAS IX - Oktaviani, Dwi; Candramila, Wolly; Yeni, Laili Fitri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was aimed at determining the feasibility of practical guide based on the extraction and organoleptic test on the fermented cempedak seeds (Artocarpus integer Thunb) on the sub-material Conventional Biotechnology Products for class IX of junior high school. This is a descriptive study in the form of a practical guide feasibility test. This study used a purposive sampling technique, consisting of two phases which namely instrument validation and practical guide validation. The instrument validation sheet comprises three fields and seven review criteria, validated by three validators, and the practical guide validation sheet comprises three fields and 10 review criteria, validated by five validators. The developed practical guide contains preface, practicum code of conduct, practicum title, basic competencies and indicators, practical goals, basic theory, tools and materials, work steps, observations, questions, and conclusions. There are two activities contained in the practical guide, namely the process of fermenting cempedak seeds and organoleptic test of food product. Validation data were analyzed using the Lawshe method with CVR and CVI. The instrument validation showed that the instrument is feasible to apply, and the practical guide validation is valid with the CVR value of 0.99 and thus feasible to apply in the learning process. Keywords: Conventional Biotechnology, Practical Guide, Validation